Human development and social power perspectives from South Asia - Mukherjee-Reed, Ananya. (Routledge contemporary South Asia series ;, 2008)
In South Asia and beyond, human development continues to be in a state of crisis. This book explores the unevenness of human development with respect to the question of difference. The author develops a conceptual framework that focuses on social power, whereby human development is seen as a process/es of reconstruction of the matrices of social power. The approach builds on three main components, which are applied to the South Asian reality: a relational view of difference; a transformative notion of social justice; and the notion of agency.